Линейные системы управления с нечетким параметром - Молчанюк, И.В.; Плотников, А.В. (Нелінійні коливання, 2006)
Розглядаються лiнiйнi системи управлiння з невизначеними параметрами, якi є елементами нечiткої множини. Для цiєї системи введено поняття жмутка траєкторiй i отримано деякi його властивостi. Також уведено поняття нечiткої множини досяжностi i доведено її опуклiсть та компактнiсть. We consider linear control systems with undetermined parameters. The undetermined parameters are considered as elements of a fuzzy set. For a given system, we introduce the notion of a pencil of trajectories and obtain some of its properties. Also, we introduce the notion of a fuzzy attainable set and prove that it is convex and compact.